Ethical advice in paediatric care. Issue 3 (29th November 2021) - Brierley, Joe; Cave, Emma; Archard, Dave
Abstract : The need for local ethics advice during the COVID-19 pandemic has put a spotlight on clinical ethics committees (CECs) and services. In this review, we focus on paediatric CECs that raise both generic questions and specific issues. In doing this, we acknowledge the broader roles of education, research and staff support some bioethics teams have developed but focus on the main areas of clinical ethics support to clinical teams. We raise 12 questions about the role, remit and responsibilities of CECs, provide preliminary answers to these and set out the next steps for the development of ethics support both in paediatric practice and more generally.